Resistant Non-union of Humerus After Intramedullary Nailing Treated with Locking Compression Plate with Bone Grafting With Nail in Situ and Shoulder Spica: A Case Report - Singh, Jagdeep (J Orthop Case Rep, 2017)
INTRODUCTION: Humerus non-union is a challenging situation for the surgeon and devastating and morbid situation for the patient. Surgical approach to the humerus is demanding because of the complex neurovascular anatomy and especially when previous surgeries have been attempted. CASE REPORT: We report a case of a young adult male who sustained a compound fracture of humerus shaft treated with intramedullary nailing followed by subsequent bone grafting and eventually landed up in non-union and was treated at our center by locking compression plate application with nail in situ with iliac crest autogenous bone graft followed by shoulder spica application. CONCLUSION: Although humerus nailing is a valid therapeutic option for humeral shaft fractures, compression plating is considered the gold standard and non-union secondary to failed interlocking nailing is a challenging situation.